2010
DOI: 10.1021/es1008938
|View full text |Cite
|
Sign up to set email alerts
|

Cyanotoxin Mixtures and Taste-and-Odor Compounds in Cyanobacterial Blooms from the Midwestern United States

Abstract: The mixtures of toxins and taste-and-odor compounds present during cyanobacterial blooms are not well characterized and of particular concern when evaluating potential human health risks. Cyanobacterial blooms were sampled in twenty-three Midwestern United States lakes and analyzed for community composition, thirteen cyanotoxins by liquid chromatography/mass spectrometry and immunoassay, and two taste-and-odor compounds by gas chromatography/mass spectrometry. Aphanizomenon, Cylindrospermopsis and/or Microcyst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
254
2
5

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 361 publications
(273 citation statements)
references
References 38 publications
12
254
2
5
Order By: Relevance
“…No samples exceeded even the lowest state saxitoxin threshold of 0.80 mg/L. These samples were all integrated photic zone samples and as such tend to be lower in both toxin and biomass compared to near-shore, targeted harmful algal bloom samples as has been shown by other studies (Lindon and Heiskary, 2009;Graham et al, 2010).…”
Section: Toxicity Of Cylindrospermopsins and Saxitoxinssupporting
confidence: 60%
See 4 more Smart Citations
“…No samples exceeded even the lowest state saxitoxin threshold of 0.80 mg/L. These samples were all integrated photic zone samples and as such tend to be lower in both toxin and biomass compared to near-shore, targeted harmful algal bloom samples as has been shown by other studies (Lindon and Heiskary, 2009;Graham et al, 2010).…”
Section: Toxicity Of Cylindrospermopsins and Saxitoxinssupporting
confidence: 60%
“…Previous investigations (Yilmaz et al, 2008;Williams et al, 2009;Graham et al, 2010) have documented cylindrospermopsin occurrences in Florida, the midwestern U.S. and New York (Boyer, 2007). Boyer et al (2007) reported cylindrospermopsins were detected rarely in New York (1.6%) contrasted with 22% in Florida (Williams et al, 2009).…”
Section: Cyanotoxins Were Detected In Nearly Every Us State Sampledmentioning
confidence: 93%
See 3 more Smart Citations